2017
DOI: 10.1016/j.ijrefrig.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of R450A drop-in performance in an R134a small capacity refrigeration unit

Abstract: HIGHLIGHTS R450A is tested in an R134a small capacity refrigeration unit.  Evaporating temperature is varied between -15ºC and 12.5ºC.  Average mass flow rate and cooling capacity are 9.1% and 9.9% lower for R450A.  Average compressor power consumption and COP values are 7.2 and 2.9% lower for R450A.  R450A can be considered as R134a drop-in replacement if decrease in cooling capacity is acceptable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 17 publications
1
21
0
1
Order By: Relevance
“…The focus is given to the difference between a set of condensation temperatures (representing different ambient temperatures) and the deviation between R134a and its alternatives. Experimental results using R513A and R450A at lower condensation temperatures can be found at Mota-Babiloni et al (2017b) and Makhnatch et al (2017).…”
Section: Resultsmentioning
confidence: 71%
“…The focus is given to the difference between a set of condensation temperatures (representing different ambient temperatures) and the deviation between R134a and its alternatives. Experimental results using R513A and R450A at lower condensation temperatures can be found at Mota-Babiloni et al (2017b) and Makhnatch et al (2017).…”
Section: Resultsmentioning
confidence: 71%
“…In a similar work, Makhnatch et al. 18 investigated the performance of R450A (the mixture composed of R134a and R1234ze (E), in the ratio of 42:58, by mass) as drop-in substitute for R134a in domestic refrigerators. It was reported that cooling capacity and COP of R450A were found to be lower by about 10% and 3%, respectively, when compared to R134a.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Aprea et al 17 compared the performance of a domestic refrigerator working with a refrigerant mixture composed of R1234ze (E) and R134a (in the ratio of 90:10, by mass) and reported with 14% energy savings compared to R134a. In a similar work, Makhnatch et al 18 investigated the performance of R450A (the mixture composed of R134a and R1234ze (E), in the ratio of 42:58, by mass) as drop-in substitute for R134a in domestic refrigerators. It was reported that cooling capacity and COP of R450A were found to be lower by about 10% and 3%, respectively, when compared to R134a.…”
Section: Introductionmentioning
confidence: 99%
“…They have a lower GWP values (547 and 562 for R450A and R513A, respectively), are low toxicity and non-flammable refrigerants, so they have been developed to cover air conditioning and refrigeration applications with safety. However, the energy performance of the refrigeration system and components has been studied with less coverage than that of the pure HFOs, due to the recent development of both refrigerants, and hence a few studies are available today [13][14][15][16][17].…”
Section: Accepted Manuscriptmentioning
confidence: 99%